Residence Time Distribution (RTD) model of water flooding in vertical sand column using Technetium-99m as the radiotracer / Noraishah Othman … [et al.] - Othman, Noraishah; Jasni, Nini Syaheera; Rosli, Nor Roslina; Yusoff, Nazrul Hizam; Shari, Mohamad Rabaie; Hassan, Hearie; Mahmood, Airwan Affandi; Abdullah, Nurliyana (Universiti Teknologi MARA Shah Alam, 2022)
Waterflooding is one of the secondary oil recovery methods practised in the oil and gas industry to improve the extraction of residual oil from oil reservoirs. The idea of understanding the behaviour of reservoirs should be explored further so that the appropriate action can be conducted in the targeted area to optimise oil production. Thus, the intervention of a radiotracer is introduced to provide the fluid flow details in a reservoir. In this study, Technetium-99m (Tc-99m) was used for waterflooding activity inside a fabricated sand column. Tc-99m was selected due to its availability and short-lived tracer (6 hours). It also emits gamma rays with an energy of 0.140 MeV. The sand column was compacted with a 150 µm grain size of sand and 5ml of approximately 3614MBq activity Tc-99m was injected inside the column which was arranged vertically. The Residence Time Distribution (RTD) model was developed from the results collected at the outlet of the sand column. The RTD model indicated the vertical sand column behaved as a Perfect Mixer in a Parallel (PMP) model and the RTD experiment verified the model well. The experimental RTD showed the existence of channelling that resembles the parallel paths that reduce water flooding efficiency. Moreover, the study also showed that the tracer activity can be as minimum as possible as long as it is detectable for data analysis.